Camellia sinensis (Tea): Implications and role in preventing dental decay - Goenka, Puneet; Sarawgi, Aditi; Karun, Vinayak; Nigam, Anant G.; Dutta, Samir; Marwah, Nikhil (Pharmacognosy Reviews)
Tea is one of the most commonly consumed beverages with bioactive compounds like polyphenols‑flavonoids‑catechins, which are thought to be responsible for the health benefits that have traditionally been attributed to the tea. These compounds have multi‑dimensional effects such as antibacterial action, inhibitory action on the bacterial and salivary amylase and inhibition of acid production. This article outlines the possible role of these compounds coupled with the presence of high fluoride content in tea to exhibit an anticariogenic effect.
Keywords: Anti‑cariogenicity; camellia sinensis (Tea); catechins; fluoride; health benefits